Survey on Improved Privacy Preserving in Peer-to-Peer Multimedia Distribution - N.S, Sajna.; R.Das, Annie. (IJRDO -Journal of Computer Science Engineering, 2016)
The rapid popularity of network-based multimedia applicationsposes many challenges for multimedia content providers toprovide efficient multimedia services. Recently, there are manyresearch interests in providing efficient and scalable multimediadistribution service. When selling electronic content, the merchantwould like each buyer to receive a same copy of the contentfingerprinted with different serial number, in order to be able totrace redistributors should illegal redistribution happen.Fingerprinting schemes used to detect illegal redistributingmultimedia data by enabling the original merchant of themultimedia data to identify the original buyer of a redistributedcopy. Anonymous fingerprinting is a convenient solution for thelegal distribution of multimedia contents with copyrightprotection while preserving the privacy of original buyers, whoseidentities are only revealed in case of illegal re-distributionhappens